2019
DOI: 10.3390/f10090803
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Experiments for Evaluating the Effects of Trees, Increasing Temperature, and Soil Texture on Carbon Stocks in Agroforestry Systems in Kerala, India

Abstract: Research Highlights: Agroforestry systems in the humid tropics have the potential for high rates of production and large accumulations of carbon in plant biomass and soils and, thus, may play an important role in the global C cycle. Multiple factors can influence C sequestration, making it difficult to discern the effect of a single factor. We used a modeling approach to evaluate the relative effects of individual factors on C stocks in three agricultural systems in Kerala, India. Background and Objectives: Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…This is congruent with robust evidence which suggests that drought could reduce soil biota productivity in TAFS, as indicated by declining soil CO 2 efflux, although only under severe drought (van Straaten et al, 2010). Similarly, model simulations suggested that increases in air temperature will drastically decrease soil C content, but only under a considerable temperature increase (+6 • C) as opposed to a marginal increase (+2 • C) (Russell and Kumar, 2019). In contrast, Andriamananjara et al (2019) suggested that temperature increase (+10 • C) will increase soil C and N content, possibly through increased soil biota activity and mineralization rates.…”
Section: Impacts Of Climate Change On Soils In Tafssupporting
confidence: 83%
See 2 more Smart Citations
“…This is congruent with robust evidence which suggests that drought could reduce soil biota productivity in TAFS, as indicated by declining soil CO 2 efflux, although only under severe drought (van Straaten et al, 2010). Similarly, model simulations suggested that increases in air temperature will drastically decrease soil C content, but only under a considerable temperature increase (+6 • C) as opposed to a marginal increase (+2 • C) (Russell and Kumar, 2019). In contrast, Andriamananjara et al (2019) suggested that temperature increase (+10 • C) will increase soil C and N content, possibly through increased soil biota activity and mineralization rates.…”
Section: Impacts Of Climate Change On Soils In Tafssupporting
confidence: 83%
“…Whether these tree species increase or decrease in their aboveground carbon may also vary depending on the different future climate scenarios they are exposed to; however, in Kenya, all these tree species except Albizia gummifera may decline in aboveground carbon irrespective of the different climate scenarios. In contrast, similarly robust evidence suggests that aboveground carbon in TAFS in India could remain unchanged (Russell and Kumar, 2019), whilst in Nigeria forecasted declines in rainfall amounts during the hottest months could reduce the land suitable for supporting Garcinia kola by up to 35.8% based on LoE3 evidence (Agwu et al, 2020). These findings indicate that the future impacts of climate change could be positive, negative or have no effect on tree distribution and size.…”
Section: The Impacts Of Climate Change On Tafs Treesmentioning
confidence: 97%
See 1 more Smart Citation
“…reported that about 37.3 and 44.1 Mg C ha -1 could be sequestered through the maintenance of 50 year long green space project in Germany. Russell and Kumar (2019) reported that if the selection of trees has the capacity of increased carbon sequestration, like higher lignin composition, supplied with efficient management methods can achieve substantial carbon storage even in the simulated tree crop ecosystem and agricultural fields. Rubber trees also have higher lignin content, which can be selected for the selection of urban trees, and the rubber ecosystem is comparatively eco-friendly (Jacob, 2003b).…”
Section: Resultsmentioning
confidence: 99%